2014
DOI: 10.1007/s00572-014-0567-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecto- and arbuscular mycorrhizal symbiosis can induce tolerance to toxic pulses of phosphorus in jarrah (Eucalyptus marginata) seedlings

Abstract: In common with many plants native to low P soils, jarrah (Eucalyptus marginata) develops toxicity symptoms upon exposure to elevated phosphorus (P). Jarrah plants can establish arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) associations, along with a non-colonizing symbiosis described recently. AM colonization is known to influence the pattern of expression of genes required for P uptake of host plants and our aim was to investigate this phenomenon in relation to P sensitivity. Therefore, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 53 publications
5
36
1
1
Order By: Relevance
“…AM symbiosis has been shown to reduce assimilation of other adverse heavy metals, such as copper, chromium, cadmium and cobalt [19,36,77]. It has been suggested that altered phosphate transport during AM colonization alleviates symptoms of phosphate toxicity in highly-fertilized soils [76]. AMF have also been suggested to reduce host sulphur starvation responses via AM-transport of sulphur-containing compounds [74,75].…”
Section: Positive Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…AM symbiosis has been shown to reduce assimilation of other adverse heavy metals, such as copper, chromium, cadmium and cobalt [19,36,77]. It has been suggested that altered phosphate transport during AM colonization alleviates symptoms of phosphate toxicity in highly-fertilized soils [76]. AMF have also been suggested to reduce host sulphur starvation responses via AM-transport of sulphur-containing compounds [74,75].…”
Section: Positive Effectsmentioning
confidence: 99%
“…AMF may also have potential for phytoremediation [36][37][38]; however, this review focusses on approaches that could be taken by crop breeding rather that adding AMF to soil. [4,[60][61][62][63][64][65][66] Water acquisition [67,68] Zinc acquisition [5,6] Drought tolerance [67,68] Salinity tolerance [29,[69][70][71] Reduced arsenic toxicity [72,73] Reduced sulphur starvation [74,75] Reduced phosphate toxicity [76] Reduced assimilation of adverse heavy metals [19,36,77] Disease resistance Increased resistance to root [31,[78][79][80] and foliar [81][82][83][84][85] pathogens Reduced arbuscular mycorrhizal colonization in mlo mutants [86] Jasmonic acid production [87][88][89][90] Components required for AM colonization used by pathogens, Golovinomyces cichoracerum (DC.) V.P.…”
Section: Introductionmentioning
confidence: 99%
“…This AMF species has been found in old‐fields elsewhere including those at Cedar Creek USA (Johnson, Zak, Tilman, & Pfleger, ). Scutellospora calospora can form associations with jarrah (Eucalyptus marginata) seedlings (Kariman, Barker, Finnegan, & Tibbett, ), and we expected it would form associations with the four myrtaceous species and two Acacia species planted in our experiment. Rhizobia tend to be generalists in their associations with legumes (incl.…”
Section: Methodsmentioning
confidence: 98%
“…The cooccurrence of AMF and EcM fungi in the same root system shows that the capability to form AM has been maintained to some degree in plant taxa which are typically EcM (Moyersoen and Fitter, 1999). However, the role of AMF in such tree species has been a matter of controversy during the past decades due to inconsistent results (Kariman et al, 2014). Studies have shown positive effects of AMF on the growth of tree species that have the potential to form ectomycorrhizae under P deficient conditions (Adjoud et al, 1996;Chen et al, 2000;Kariman et al, 2014), and a succession of these mycorrhizal types has been reported during different stages of plant growth (Santos et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…However, the role of AMF in such tree species has been a matter of controversy during the past decades due to inconsistent results (Kariman et al, 2014). Studies have shown positive effects of AMF on the growth of tree species that have the potential to form ectomycorrhizae under P deficient conditions (Adjoud et al, 1996;Chen et al, 2000;Kariman et al, 2014), and a succession of these mycorrhizal types has been reported during different stages of plant growth (Santos et al, 2001). Investigations on the influence of DSE fungi on plant growth further indicate that inoculation with these fungi can increase biomass as well as nutrient content of plants (see Newsham, 2011 and references therein).…”
Section: Introductionmentioning
confidence: 99%